2003
DOI: 10.1038/sj.ejcn.1601496
|View full text |Cite
|
Sign up to set email alerts
|

Serum transferrin receptor in children with respiratory infections

Abstract: Objective: To study the effect of infection on iron status in children suffering from acute, mild or severe respiratory infections and to determine the nature of anemia in infection using serum transferrin receptor (sTfR) levels. Design: Forty-three children aged between 3 and 5 y with no evidence of infection and receiving iron supplements in the preceding 100 days served as controls. Twenty-one children with mild upper respiratory infection and 94 children hospitalized for acute pneumonia constituted the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
3
14
0
2
Order By: Relevance
“…The results of examinations of other authors also demonstrate the usefulness of sTfR concentrations and sTfR/ /logF values in differentiating IDA from IA, as no increase in either parameter was observed in patients with infectious anemia without iron deficiency [27,[42][43][44].…”
Section: Discussionmentioning
confidence: 65%
“…The results of examinations of other authors also demonstrate the usefulness of sTfR concentrations and sTfR/ /logF values in differentiating IDA from IA, as no increase in either parameter was observed in patients with infectious anemia without iron deficiency [27,[42][43][44].…”
Section: Discussionmentioning
confidence: 65%
“…Thus, in present study the prevalence of iron defi ciency anaemia itself is lower than that reported in general (67-77%) 8 which might be due to usage of a strict criteria of combina on of serum ferri n<12 ng/ml and RDW>15%. As aforemen oned, the combined criteria is more specifi c and rules out the chance higher prevalence of IDA 9 . Prevalence of iron defi ciency anaemia as per our criteria in present study was 32% in cases and 24% in control group, however, the diff erence was not signifi cant sta s cally though children with iron defi ciency anaemia were at a higher risk of wheeze associated respiratory diseases (OR=1.49; 95% CI 0.62-3.59).…”
Section: Discussionmentioning
confidence: 99%
“…Tujuh puluh lima anak dengan data lengkap dan Dampak negatif yang diakibatkan oleh ADB pada anak balita berupa gangguan konsentrasi belajar, tumbuh kembang terganggu, penurunan aktifitas fisik maupun kreatifitas menurun, serta menurunkan daya tahan tubuh sehingga meningkatkan risiko infeksi. 2,4 Atas dasar angka kejadian ADB yang tinggi dan dampak negatif yang ditimbulkannya, maka kami melakukan penelitian yang bertujuan untuk mendapatkan gambaran hematologi anemia defisiensi besi pada anak yang dirawat di RSUD Wangaya Denpasar.…”
Section: Hasilunclassified